Reduced High Shear Platelet Adhesion to the Vascular Media: Defective von Willebrand Factor Binding to the Interstitial Collagen - Komorowicz, Erzsebet; McBane, Robert D., II; Charlesworth, Jon; Fass, David N. (Thrombosis and Haemostasis, 2002)
Fibrillar collagen serves as a thrombogenic surface for platelet adhesion mediated by von Willebrand factor (vWf) at high shear. Although abundant throughout the arterial wall, vWf-dependent platelet deposition to artery cross-sections from perfused citrated blood is localized to the adventitia of the vessel wall. Here we describe a similarly skewed distribution of vWf-binding sites in artery cross-sections. Binding of vWf-coated fluorescent beads, as well as detection of plasma vWf bound to artery cross-section at 3350 s−1 shear rate with indirect particle-immunofluorescence or immunoelectron microscopy demonstrate vWf binding sites in the adventitia, but not in the media. A monoclonal anti-vWf antibody that interferes with vWf-binding to collagen in a microplate ELISA inhibits vWf-binding to both the adventitia and sections of collagen fibrils. Our data suggest that the media, despite its fibrillar collagen content, evidenced by electron microscopy, is defective for vWf-binding, which may explain its thromboresistant nature at high shear rates.
Keywords: Willebrand; collagen; adhesion; platelet; media